2010
DOI: 10.1002/hbm.20950
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation of abstract and concrete concepts: A meta‐analysis of neuroimaging studies

Abstract: A number of studies have investigated differences in neural correlates of abstract and concrete concepts with disagreement across results. A quantitative, coordinate-based meta-analysis combined data from 303 participants across 19 functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) studies to identify the differences in neural representation of abstract and concrete concepts. Studies that reported peak activations in standard space in contrast of abstract > concrete or concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
362
6
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(434 citation statements)
references
References 85 publications
61
362
6
5
Order By: Relevance
“…In contrast, our set of words included many abstract concepts, such as "justice" and "desire" (see Table S1 for full list). This suggestion is supported by a meta-analysis that contrasted regions involved in abstract versus concrete words, and that found clear evidence that the TP was more active in response to abstract words, whereas ventral temporal regions showed a preference for concrete words (20).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, our set of words included many abstract concepts, such as "justice" and "desire" (see Table S1 for full list). This suggestion is supported by a meta-analysis that contrasted regions involved in abstract versus concrete words, and that found clear evidence that the TP was more active in response to abstract words, whereas ventral temporal regions showed a preference for concrete words (20).…”
Section: Discussionmentioning
confidence: 73%
“…Computational models of semantic cognition propose that concepts are represented by a similarity-based code in an amodal "semantic hub," situated in the apex of the ventral processing stream in the temporal pole (TP) (17,18). Although other regions, such as the temporo-parietal cortex (19), have also been linked to the representation of abstract conceptual knowledge, the TP is most consistently implicated in both patient and neuroimaging studies (17,20,21).These computational models therefore make clear predictions about the expected neural basis of semantic false memory. Namely, the TP semantic hub should contain a similarity-based code, such that the neural representations of DRM words reflect the known semantic relatedness between those words.…”
mentioning
confidence: 99%
“…Lieberman, 2012a,b;Spunt and Adolphs, 2014). These regions partially overlap with several meta-analytically defined functional networks, including: (i) the so-called 'theory-of-mind' or 'mentalizing' network associated with tasks of mental-state reasoning (Gallagher and Frith, 2003;Amodio and Frith, 2006;Saxe, 2006;Carrington and Bailey, 2009;Van Overwalle and Baetens, 2009;Schurz et al, 2014); (ii) the default mode network (DMN), especially its dorsomedial PFC component (Raichle et al, 2001;Buckner et al, 2008;Andrews-Hanna et al, 2010; (iii) the network associated with mentally simulating episodes both past and future (Hassabis and Maguire, 2007;Spreng et al, 2009;Schacter et al, 2012); (iv) the network associated with comprehending narrative discourse (Ferstl and von Cramon, 2001;Ferstl et al, 2008;Mar, 2011;Nijhof and Willems, 2015); (v) the network associated with transmodal semantic processing (Binder et al, 2009;Binder and Desai, 2011) and (vi) the network associated with comprehending abstract compared to concrete words (Binder et al, 2009;Wang et al, 2010;Binder and Desai, 2011). Decreasing LOAs were associated with the majority of the left hemisphere regions reliably associated with the How > Why contrast in previous work.…”
Section: Brain Regions For Conceptualizing An Action At Different Loasmentioning
confidence: 99%
“…However, these regions of the semantic network are recruited differently depending of the type of stimuli that are processed. For instance, differences of activation in ATL and IPC have been reported between concrete and abstract words in neuroimaging studies, using functional magnetic resonance imaging or positron emission topography (Hoffman, Binney, & Lambon Ralph, 2014;Sabsevitz, Medler, Seidenberg, & Binder, 2005;Wang, Conder, Blitzer, & Shinkareva, 2010). Studies on clinical patients, with lesions in regions of the semantic network also showed differences in performance during semantic processing of abstract and concrete words (Loiselle, et al, 2012).…”
Section: Introductionmentioning
confidence: 98%